The prognostic role of lymphovascular invasion and lymph node metastasis in perihilar and intrahepatic cholangiocarcinoma. Issue 8 (August 2019) - Lurje, Georg; Bednarsch, Jan; Czigany, Zoltan; Lurje, Isabella; Schlebusch, Ivana Katharina; Boecker, Joerg; Meister, Franziska Alexandra; Tacke, Frank; Roderburg, Christoph; Den Dulk, Marcel; Gaisa, Nadine Therese; Bruners, Philipp; et al.
Abstract: Introduction: Cholangiocellular carcinoma (CCA) is an aggressive malignancy with a dismal prognosis. Among curative treatment options for CCA, radical surgical resection with extrahepatic bile duct resection, hepatectomy and en-bloc lymphadenectomy are considered the mainstay of curative therapy. Here, we aimed to identify prognostic markers of clinical outcome in CCA-patients who underwent surgical resection in curative intent. Material and methods: Between 2011 and 2016, 162 patients with CCA (perihilar CCA (pCCA): n = 91, intrahepatic CCA (iCCA): n = 71) underwent surgery in curative intent at our institution. Preoperative characteristics, perioperative data and oncological follow-up were obtained from a prospectively managed institutional database. The associations of overall- (OS) and disease-free-survival (DFS) with clinico-pathological characteristics were assessed using univariate and multivariable cox regression analyses. Results: The median OS and DFS were 38 and 36 months for pCCA and 25 and 13 months for iCCA, respectively. Lymphovascular invasion (LVI) and lymph node metastasis as well as surgical complications as assessed by the comprehensive complication index (CCI) and tumor grading were independently associated with OS for the pCCA (LVI; RR = 2.36, p = 0.028; CCI; RR = 1.04, p < 0.001) and iCCA cohorts (N-category; RR = 3.21, p = 0.040; tumor grading; RR = 3.75, p = 0.013; CCI, RR = 4.49, p = 0.010), respectively. No other clinical variable including R0-status and Bismuth classification was associated with OS. Conclusion: Major liver resections for CCA are feasible and safe in experienced high-volume centers. Lymph node metastasis and LVI are associated with adverse clinical outcome, supporting the role of systematic lymphadenectomy. The assessment of LVI may be useful in identifying high-risk patients for adjuvant treatment strategies.